PENINGKATAN PENERIMAAN ZIS MELALUI PLATFORM DIGITAL SEBAGAI PENDUKUNG UPAYA PEMULIHAN EKONOMI UMAT DI TENGAH PANDEMI COVID-19 - Tata Wulandari (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
The government continues to carry out economic recovery efforts amid the COVID-19 pandemic. The increase in ZIS revenue is directly proportional to the increase in ZIS distribution. This is a new hope for people who have been badly affected by the pandemic so that their economy can recover. The use of digital platforms also supports the increase in ZIS revenue. This research is a descriptive qualitative research and is literature research. Conclusions are drawn from the data that has been collected and analyzed. The results of the discussion show that the use of digital platforms has a significant impact on the economic recovery of the people in the midst of the COVID-19 pandemic. There is great hope for all parties, especially the amil zakat institutions and also all people, for the contribution of digital platforms to increasing ZIS revenue so that in the future Indonesia's economic conditions will improve. Keywords : ZIS, Digital Platforms, Economic Recovery, covid-19